Comprehensive evaluation and screening of drought resistance in maize at germination and seedling stages - Du, Wentao; Zhang, FuLai; Zhang, Lei; Hu, Mengting; Tian, Huijuan; Hao, Ying; Ding, Shuqi; Zhang, Dan (Frontiers in Plant Science, 2025)
IntroductionMaize is one of the most important staple crops globally, but drought stress has emerged as a major abiotic factor limiting its productivity.MethodsThis study, conducted in 2023 at the Key Laboratory of Genetic Improvement and Efficient Production of Specialty Crops in Southern Xinjiang Arid Regions, College of Agriculture, Tarim University, aimed to identify key drought-tolerant traits and maize varieties. Drought stress was applied during the germination and seedling stages, and 15 drought resistance indices, including germination rate (GR), germination energy (GE), plumule length, plant height (PH), and chlorophyll content (ChL), were comprehensively evaluated.ResultsDrought stress significantly reduced GR, GE, and the germination index, while also inhibiting coleoptile and radicle growth. It further impeded seedling development, as evidenced by decreased PH, reduced ChL content, and lower biomass accumulation. Correlation analysis showed varying degrees of association among the 15 drought resistance indices. Principal component analysis grouped these indices into five composite components, accounting for 75.22% of the total cumulative variance. Stepwise regression analysis produced the following equation: D = -0.002 + 0.13×GEI + 0.938×RFWI + 0.115×RLI + 0.112×DWPI + 0.097×ChlI. Based on the D values, cluster analysis classified 41 maize germplasm resources into five categories: extremely drought-tolerant, strongly drought-tolerant, moderately drought-tolerant, drought-sensitive, and highly drought-sensitive. The extremely drought-tolerant varieties included Yuanyuan 1, Ximon 6, Jinongyu 309, Nongkeyu 368, Xuanhe 8, Hengyu 369, and Nongfu 99.DiscussionThese findings provide a theoretical foundation for breeding drought-resistant maize and identifying drought-tolerant genotypes.